Preliminary Study on the Distribution of the Introduced Gall-forming Fly, Cecidochares connexa (Macquart) (Diptera Tephritidae) for the Biological Control of the Invasive Alien Weed Chromolaena odorata (L.) R.M. King & H. Rob. (Asteraceae) in the Philippines (2019)
The distribution of Cecidochares connexa (Macquart), a biological control agent of the invasive plant Chromolaena odorata (L.) R.M. King & H. Rob. was determined around the three main islands – Luzon, Visayas, and Mindanao – in the Philippines. A total of 105 sites in 17 localities with C. odorata were surveyed for the presence of C. connexa. Cecidochares connexa was present at 82 sites in eight localities, limited to around Visayas and Mindanao. Some sites where the gall fly was reported were up to 400 km from the initial release sites around Davao, Mindanao. Cecidochares connexa was not found at any of the nine localities surveyed around Luzon. Visual observations showed that the gall fly is having some impact on C. odorata, as evidenced by dead branches and stems. These results show that C. connexa has firmly established in the country and that it has the ability to disperse long distances to new areas. It is likely that C. connexa will continue to disperse further with time. However, a more robust study regarding its presence in other parts of the country and its effectiveness as a biological control agent is needed.